LEARNING AND PROBLEM SOLVING BY RETARDED AND NORMAL Ss. - Miller, Leon K.; Hale, Gordon A.; Stevenson, Harold W. (American Journal of Mental Deficiency, 1968)
The article examines the learning and problem solving capabilities of retarded and normal people. Comparisons of the two groups revealed few significant differences in paired associate and discrimination learning but markedly poorer performance was observed in retarded than in normal people on tasks involving the concept of conservation, the concept of probability, verbal memory, and anagrams. Retarded individuals have impaired ability to use verbal symbols as a means of controlling behavior and of abstracting from previous experiences.